2006
DOI: 10.1242/dev.02218
|View full text |Cite
|
Sign up to set email alerts
|

Frizzled5/8 is required in secondary mesenchyme cells to initiate archenteron invagination during sea urchin development

Abstract: Wnt signaling pathways play key roles in numerous developmental processes both in vertebrates and invertebrates. Their signals are transduced by Frizzled proteins, the cognate receptors of the Wnt ligands. This study focuses on the role of a member of the Frizzled family, Fz5/8, during sea urchin embryogenesis. During development, Fz5/8 displays restricted expression, beginning at the 60-cell stage in the animal domain and then from mesenchyme blastula stage, in both the animal domain and a subset of secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 73 publications
6
86
0
Order By: Relevance
“…Similarly, early expression of a fzd gene, fzd9/10, terminates after 15 h, and only one fzd gene, fzd5/8, is transcribed after 21 h in a subset of mesodermal cells located in the oral portion of the veg2 mesoderm. This finding is consistent with earlier results (22). No sfrp or dkk genes are expressed in Veg2 mesodermal cells after 15 h. Thus, with the exception of oral mesodermal cells, most mesodermal cells express neither wnt nor fzd genes from 18 h to gastrulation and are not likely to send or receive Wnt signaling.…”
Section: Resultssupporting
confidence: 93%
“…Similarly, early expression of a fzd gene, fzd9/10, terminates after 15 h, and only one fzd gene, fzd5/8, is transcribed after 21 h in a subset of mesodermal cells located in the oral portion of the veg2 mesoderm. This finding is consistent with earlier results (22). No sfrp or dkk genes are expressed in Veg2 mesodermal cells after 15 h. Thus, with the exception of oral mesodermal cells, most mesodermal cells express neither wnt nor fzd genes from 18 h to gastrulation and are not likely to send or receive Wnt signaling.…”
Section: Resultssupporting
confidence: 93%
“…First, apical pole genes, which are those that are expressed at the animal most ectodermal region (such as Fz5/8 [15] and SpNK2.1 [30]), are eliminated. As shown in detail in Table 2, the expression ratios in lithium-treated embryos for newly discovered apical plate markers such as FoxQ2 , Zfhpf4 (Figure 6), and Dp-Hbn (WISH database [22]) are 0.15, 0.01, and 0.05, respectively, which correspond to 6-fold, 100-fold, and 20-fold downregulation, respectively (as determined by Q-PCR).…”
Section: Resultsmentioning
confidence: 99%
“…As a control, we measured Spec2a expression in zinc-treated embryos and find that it is about tenfold upregulated (Table 2). One transcription factor that is expressed in the aboral ectoderm but that is also expressed in other territories is the T-box gene Tbx2 / 3 [15,33]. This gene was found to be significantly downregulated (Table 2; namely, clone RUDIREA_28I11, which is downregulated by a factor of 0.20; P = 3.50 e-12 ) in lithium-treated embryos and is upregulated in zinc-treated embryos.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SMC derivatives include pigment cells, which ingress at various times during gastrulation in different species (Gibson and Burke, 1985;Takata and Kominami, 2004), blastocoelar cells (Tamboline and Burke, 1992), esophageal muscle precursors (Ishimoda-Takagi et al, 1984;Wessel et al, 1990;Venuti et al, 1993), and cells expressing the 5-hydroxytryptamine receptor (Katow et al, 2004) At least some of the SMC derivatives that express Lv-snail mRNA and protein are likely to be pigment cells, because some Lv-snailexpressing cells are embedded in the ectoderm, and because in nickeltreated embryos, which largely lack pigment (Hardin et al, 1990;Takata and Kominami, 2004), Lv-snail is down-regulated. The small number of SMCs that express Lv-snail compared with other more general markers for SMCs, such as Frizzled5/8 (Croce et al, 2006) and most SMC markers identified using macroarray approaches (Calestani et al, 2003) suggests that Lv-snail is only expressed in a subset of SMCs. Based on our situ hybridization results, Lv-snail is detectable mainly in SMCs that ingress late in gastrulation, a population that has been suggested to be a reserve population of cells capable of "converting" to the skeletogenic fate (Ettensohn and .…”
Section: Functions Of Snail During Secondary Mesenchyme Cell Differenmentioning
confidence: 99%